( | 3 | − | x | ) | ÷ | 5 | = | ( | - | 2 | − | 3 | x | ) | ÷ | 4 |
Left side of the equation = | 3 | × | 1 5 | − | x | × | 1 5 |
= | 3 5 | − | x | × | 1 5 |
3 5 | − | 1 5 | x | = | ( | - | 2 | − | 3 | x | ) | ÷ | 4 |
Right side of the equation = | - | 2 | × | 1 4 | − | 3 | x | × | 1 4 |
= | - | 1 2 | − | 3 4 | x |
3 5 | − | 1 5 | x | = | - | 1 2 | − | 3 4 | x |
- | 1 5 | x | + | 3 4 | x | = | - | 1 2 | − | 3 5 |
11 20 | x | = | - | 1 2 | − | 3 5 |
11 20 | x | = | - | 11 10 |
x | = | - | 11 10 | ÷ | 11 20 |
= | - | 11 10 | × | 20 11 |
= | - | 1 | × | 2 |
x | = | - | 2 |